KONDISI DAN STRATEGIS PENGELOLAAN KOMUNITAS PADANG LAMUN DI WILAYAH PESISIR KOTA DENPASAR, PROVINSI BALI - Sudiarta, I Ketut; Restu, I Wayan (Bumi Lestari; Vol 11 No 2 (2011), 2011)
A study on condition and management strategy for sea grass community was undertaken on the beach area of Denpasar City, Bali Province between March and June, 2010. The study was undertaken on two locations: Sanur and Serangan beaches. Aim of the study was to find out recent condition, problems related to sea grass and set up its management strategy. The study was utilising Transect Plot methods. Six sampling stations was determined. Identification of condition and degradation of sea grass community was undertaken by retrospective approaches. Data analyses was undertaken by utilising kualitative and kuantitative approaches; refering to determination of â€œKriteria Baku Kerusakan dan Pedoman Penentuan Status Padang Lamunâ€ (the standard criteria for damage and manual for determination of the status of sea grass) refering to Decission of State Minister on Environment Number 200 year 2004 and cualitative ecology index and analogist comparative approach on formulating management strategy. Species richness of sea grass on beaches of Denpasar city was 10 out of 12 of those existed in Indonesia, namely: Zostera sp., Halodule pinifolia, Halodule uninervis, Cymodocea rotundata, Cymodocea serrulata, Syringodium isoetifolium, Thalassodendron ciliatum, Enhalus acoroides, Halophila ovalis and Thalassia hemprichii. Species density of sea grass varied across locations and observation stations, ie. Sanur beach (209 individual/sq.m) and Serangan Island (276 ind/sq.m); with the higest density made by Cymodocea rotundata. Persentage of sea grass cover on the beach of Denpasar was between 28.79% â€“ 42.74%, with the highest at Serangan-III and the lowest at Sanur-I. Based on the cover, the status of condition of sea grass on the beach area of Denpasar was classified into the category of bad/poor -moderate/less healthy. The average score of level of damage of sea grass on the beach area of Denpasar varied between 8.89 % â€“ 15.79 %, which was within the category of low level of damage, where the highest level of damage was at Station I of â€œPerairan Seranganâ€ and the lowest at Serangan II-III, where there were no damage reported to occur. The change in domination of sea grass in Sanur and Serangan from Enhalus acoroides into Cymodocea rotundata and Thalassia hemprichii was observed because the change in the texture of substrate after reclamation of the beach and sedimentation. Human activities which caused damage of sea grass on Sanur and Serangan beaches such as anchoring the fishermanâ€™s canoes, propeler boats, crib constructions, break water and beach reclamations. For keeping the sea grass ecosystem of Denpasar sustainable, it is recommended for a better management of beaches/sea on the area where sea grass grows and implementing strategy of integrated management of sea grass with integrated coastal and sea management.
Keywords: sea grass, status of condition, damage level, management strategy